PENILAIAN KINERJA KEUANGAN PADA KP3Y (Koperasi Produksi Pengusaha Perak Yogyakarta) di Kotagde YogyakartaTahun 2012-2016 - Muhammad Sirajuddin (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this research is to determine the financial performance of KP3Y in Kotagede Yogyakarta in 2012-2016 according to Ministerial Decree of Cooperatives and Small and Medium Enterprises. 20 / Per / M.KUKM / XI / 2008. This research is categorized into quantitative descriptive research, which in this study describes and explains how financial performance at KP3Y in Kotagede uses financial report as the basis of financial performance assessment. In the analysis with financial ratios according to the Ministerial Decree of Cooperatives and Small and Medium Enterprises. 20 / Per / M.KUKM / XI / 2008. The result of this research is that the ratio of KP3Y finance in Kotagede Yogyakarta, as a whole, is placing. The results of the calculation of the assessment of the research component can be concluded that the cooperative conditions in 2012 in a less healthy condition. in the year 2013-2014 in good condition because it is on score 60> x <80. While in the year 2015-2016 showed the unhealthy condition because it is on score 40> x <60.